Distinct patterns of global promoter methylation in early stage chronic lymphocytic leukemia. Issue 3 (18th December 2013) - Ronchetti, Domenica; Tuana, Giacomo; Rinaldi, Andrea; Agnelli, Luca; Cutrona, Giovanna; Mosca, Laura; Fabris, Sonia; Matis, Serena; Colombo, Monica; Gentile, Massimo; Recchia, Anna Grazia; Kwee, Ivo; et al.
<x xml:space="preserve">Abstract</x> Genomic and epigenomic studies of chronic lymphocytic leukemia (CLL) are reshaping our understanding of the disease and have provided new perspectives for a more individualized diagnosis and new potential therapeutic targets. In this study, the global promoter methylation profile was determined in highly purified B‐cells from 37 (Binet stage A) CLL patients, using high‐resolution methylation microarrays (27, 578 CpG). Overall, the methylation pattern correlated with the major biological (ZAP‐70 and CD38), and molecular (IGHV mutation) markers, distinguishing CLL cases according to IGHV mutational status. Cell adhesion molecules were enriched in the signature of unmutated (UM) versus mutated (M‐) CLL. Moreover, in M‐CLL CpG hyper‐methylation in three genes, including SPG20, was significantly anti‐correlated with the corresponding gene expression level. Finally, the correlation between the methylation pattern and clinical parameters was investigated. Notably, out of 42 methyl‐probes that were significantly associated with progression free survival (PFS), hyper‐methylation of SPG20 was also positively associated with PFS. These data support the notion that epigenetic changes have clinical impact in CLL and may contribute to the identification of novel candidate disease‐associated genes potentially useful to predict the clinical outcome of early stage CLL patients. © 2013 Wiley Periodicals, Inc.